Sustainable development: approaches from economics - Vergara Tamayo, Carlos Andrés; Ortiz Motta, Diana Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The concept of sustainable development has been the subject of extensive discussion and controversy for decades, of theoretical and practical questions and debates in Economics field. The theories that support this conceptual diversity allow to identify in the time not just the construction of the concept but also its transformation, either by disciplinary approaches as well as multidisciplinary, as a variety of positions about its evolution. From there arises the need to relate some key elements and different points of sustainable development, given the conditions that gave origin to it from Economics as social science.